The everyday life of the revolution: gender, violence and memory - Roy, Srila (Sage, 2007)
The ‘heroic life’ or the life of the revolutionary is one that resists or even seeks to transcend the everyday and the ordinary. The ‘banal’ vulnerabilities of everyday life, however, continue to constitute the unseen, often unspoken background of such a heroic life. This article turns to women’s memories of everyday life spent ‘underground’ in the context of the late 1960s radical left Naxalbari movement of Bengal. Drawing upon recent published memoirs and my own field interviews with middle class female (and male) activists, I outline the ways in which revolutionary femininity was imagined and lived in the everyday life of this political movement. I focus, in particular, on the gendered and classed nature of political labour, the gendering of revolutionary space, and finally, the extent to which everyday life in the ‘underground’ was a site of vulnerability and powerlessness, especially for women. I also signal how these memories of interpersonal conflict and everyday violence tend to remain buried under a collective mythicisation of the ‘heroic life’.